Stochastic perspective of industrial distribution network processes - Sheresheva, Marina Y.; Kolesnik, Nadezda A. (Industrial marketing management, 2011)
This article investigates contemporary distribution processes in the industrial market. The main trend in distribution during the recent decades manifests itself in a growing number of network-type distribution chains. Based on the evolutionary trends in distribution research, we came up with the idea to investigate distribution networks processes using mathematical tools of probability theory. We consider a distribution network in a stochastic way, where a focal agent optimizes the distribution chain at each decision-making node by switching between possible partners. This allows us to apply time-homogeneous Markov chains theory to explore the partner selection process. We present an approach that allows for the estimating of implicit non-price variables of partner choice in a supply chain. The approach is based on the research context of the transitional Russian economy. ► Modeling distribution network processes using tools of probability theory. ► Apply Markov chains to the process of choosing partner. ► Propose an approach to estimation non-price variables.